PROSES KOMUNIKASI INTERPERSONAL DANCER GAY - Dini Anysa; Sampoerno Sampoerno (Cakrawala Jurnal Penelitian Sosial, 2019)
Homosexual gay is a phenomenon social could no longer indisputably itsexistence. Majority of indonesian society consider homosexual as sexual perversion. But asthe developments taking place from time to time make big change with the people sexual.Tasikmalaya known to the dancer homosexual, because found any member of gay in anygroup dance joined in community dancer Tasikmalaya. Of course there is the processwhereby any member of the be a gay ‘meletek’. In the process of ‘memeletekkan’ membersof dance normal being gay need for two way communication. Communication processwas used for the interpersonal communication.Research on communication process dancer interpersonal gay with a case study‘peletek’ on a phenomenon dancer gay within the community dancer earthquake researchis the kind of research with the interpretative qualitative. To be carried out more depth,the study is done by using in depth interview focusing on life story.Based on the research done, communication process interpersonal occurring inpull to buy. Dancer gay approach of dancer normal through the process communicationinterpersonal according to 5 the effectiveness of communication interpersonal De Vito.Started by the openness, and then the empathy and the attitude mutual support andpositiveness that is implanted in self each dancer make the process ‘peletek’ closer in thetipping point. The last of equality between dancer gay and dancer normal. With his theprocess producing a change of dancer normal be a gay. A change in attitude wasinfluenced by a symbol verbal and nonverbal. Because touch and comfort, finally dancernormal ‘meletek’ has become a gay.